Pengembangan Web Alumni Dengan Menggunakan LinkedIn Pada Perguruan Tinggi - Aris Martono; Giandari Maulani; Siti Pujianingsih (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2017)
The purpose of this study is to utilize social media to create a network of alumni linkedin and job information to the network in which the activation of this as a prerequisite for taking the diploma so that it fosters an emotional bond between alumni and the university. The method used is surveymethod with observation and interviews with literature. Then analysis system to identify the weaknesses in the system and the information needs of its users. The results of this analysis is that every student can perform activation on the alumni web to take a diploma requirements, establish communication among alumni, students and faculty as well as notifications of incoming mail to each member on job vacancies. The disadvantage is social media is new and only professional people who know. Implementation of this system in the form of web alumni who provide facilities such as linkedin regenerate the access token, looking for names of alumni, the alumni profile, menu provided by the company and job profile and job application that is included in each profile alumni. The existence of the alumni web by using this linkedin, each alumnus can obtain job information and company profile and can communication between alumni and the university.